Redesain Kantor Bupati Kabupaten Sumedang Dengan Pendekatan Aktivitas - Permata Ramadhani, Azizatulatifah; Nur Sheha Gunawan, Ahmad; Bayu Perdana, Aditya (Telkom University, 2024)
The Sumedang Regency Government Office located on Jl. Prabu Gajah Agung, North Sumedang, has a three-story building with an area of 7,883 m² and operates from Monday to Friday. This office has implemented an Electronic-Based Government System (EGS), which changes the way of working from manual to digital, reduces paper use and increases the need for supporting facilities for changes in the way of working. Based on the data obtained, inefficient zoning-blocking, lack of office facilities, lighting in several rooms does not meet standards, soundproofing is ineffective, and security and ventilation systems need improvement. This study identified the need for lighting improvements, and improvements to acoustic facilities, and ventilation. Redesign with the theme of optimization of space based on activity with the aim of increasing the comfort and efficiency of the workspace of the Regent, his assistant, as well as meeting and guest rooms, with the aim of creating a more productive work environment and in accordance with applicable standards. Keywords: Interior, SPBE, facility, activity, standard